onirama2 (ΔΗΜΟΣ ΑΓΡΙΝΙΟΥ ΤΜΗΜΑ ΠΛΗΡΟΦΟΡΙΚΗΣ, 2017)
: than when you feel that the only way is the sky Just remember you only live once than when you wanna live forever When you know how all you need is love Just remember you only live once you live once Πέταξε, πέταξε, πέταξε...